Polyaniline crystalline nanostructures dependent negative permittivity metamaterials. (3rd February 2020) - Xu, Xiaojiang; Fu, Qiangang; Gu, Hongbo; Guo, Ying; Zhou, Heng; Zhang, Jiaoxia; Pan, Duo; Wu, Shide; Dong, Mengyao; Guo, Zhanhu
Abstract: Herein, we report the preparation of polyaniline (PANI) crystalline nanostructures and their dependent negative permittivity. By controlling the types of doped acids and the doping levels, PANI nanostructures with different crystallinity degrees are synthesized and composed of alternating metallic islands and amorphous regions confirmed by high resolution transmission electron microscopy (HRTEM). It's found that 0.15 mol L −1 of p -toluenesulfonic acid (PTSA) as doped acid is the optimal concentration to achieve a proper molecular weight (226, 904 g mol −1 ) and higher degree of crystallinity (33.4%) from X-ray diffraction (XRD) for PANI. With further increasing the concentration of PTSA to 0.30 mol L −1, the degree of crystallinity (37%) of PANI has little change, but its molecular weight is quickly decreased to 35, 102 g mol −1 . As a consequence, the electrical conductivity of PANI increases from 1.1 × 10 −3  S cm −1 for poly (2-acrylamido-2-methyl-1-propanesulfonic acid) ( p -AMPS) to 6.9 S cm −1 for PTSA and the PANI crystalline nanostructures doped with PTSA and hydrochloric acid possess a negative permittivity within the measured frequency range of 20 Hz to 2 MHz, whereas the permittivity for PANI doped with perchloric acid, phosphoric acid, camphorsulfonic acid, and p -AMPS switches from negative at low frequency to positive at high frequency. By calculation from AC conductivity, the charge carrier transport in these PANI systems follows the polaron hopping transport mechanism. Graphical abstract: Image 1 Highlights: Negative permittivity of polyaniline (PANI) could be tuned via PANI nanostructures. The influences of the doped acid types and doping degrees on the structure of PAN were studied. The PANI nanostructures were composed of alternating metallic island and amorphous regions. The charge carrier transport in these PANI systems followed the polaron hopping transport mechanism.